2005
DOI: 10.1007/s11199-005-1198-3
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Myths, Sexuality Misconceptions, Information Sources, and Risk Perceptions of Bodabodamen in Southwest Uganda

Abstract: This article reports findings from a study conducted among 212 private motorbike-taxi riders, locally called bodabodamen, from two study sites-a slum area and the urban center of Masaka town. Qualitative and quantitative methods were triangulated; a questionnaire, focus group discussions, in-depth interviews, case studies, and interactive workshops were all used. There were high levels of awareness of HIV, much more than sexually transmitted diseases (STDs), because many participants had closely experienced HI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…Like most studies, 20,22,41,42 the narratives of our male participants highlight the fact that it is predominantly adolescents (often students) who have abortions in this context. This confirms other reports from Uganda, which claim that 54% of women have their first birth before the age of 18 years, 43% of 15-19-year-olds begin childbearing, and complications of pregnancy, childbirth and unsafe abortions are the major causes of abortion for women aged 15-19 years.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Like most studies, 20,22,41,42 the narratives of our male participants highlight the fact that it is predominantly adolescents (often students) who have abortions in this context. This confirms other reports from Uganda, which claim that 54% of women have their first birth before the age of 18 years, 43% of 15-19-year-olds begin childbearing, and complications of pregnancy, childbirth and unsafe abortions are the major causes of abortion for women aged 15-19 years.…”
Section: Discussionmentioning
confidence: 59%
“…However, their attitudes towards contraception were highly ambivalent, their use was mostly sporadic, and their knowledge was highly erroneous. 42 The rampant sexual activity, in combination with low regard for contraception, perhaps explain the prevalent necessity of recourse to abortion as an inevitable and ultimate solution for unwanted sexual health problems. Just as contraception was relegated to the female domain 42 , preliminary data analysis revealed that participants were pushing issues surrounding abortion into the realm of women.…”
Section: Discussionmentioning
confidence: 99%
“…Sexual myths are often exaggerated, incorrect and unscientific ideas, symbols, feelings (guilt, inadequacy, anxiety, fear of failure) on sexual topics that people believe to be true [9]. They are predetermined judgments that limit the free experience of sexuality [4,10,11].…”
mentioning
confidence: 99%
“…These misinformed beliefs and false ACCEPTED MANUSCRIPT ACCEPTED MANUSCRIPT 4 expectations can affect the attitudes and behaviors of individuals regarding their sexuality (Nyanzi et al, 2005;Baker, & DeSilva, 1988;Nobre, Pinto-Gouveia, & Gomes, 2003). The exact effect of beliefs on sexual functioning is beginning to attract attention following some clinical studies.…”
Section: Introductionmentioning
confidence: 99%